2007
DOI: 10.1186/1471-2202-8-21
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal integration of tactile information in human somatosensory cortex

Abstract: Background: Our goal was to examine the spatiotemporal integration of tactile information in the hand representation of human primary somatosensory cortex (anterior parietal somatosensory areas 3b and 1), secondary somatosensory cortex (S2), and the parietal ventral area (PV), using high-resolution whole-head magnetoencephalography (MEG). To examine representational overlap and adaptation in bilateral somatosensory cortices, we used an oddball paradigm to characterize the representation of the index finger (D2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
68
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 85 publications
5
68
2
Order By: Relevance
“…3). The mid-latency somatosensory P100 is assumed to be generated in bilateral secondary somatosensory cortex (Tarkka, Micheloyannis, & Stokić , 1996;Valeriani, Fraioli, Ranghi, & Giaquinto, 2001;Frot, Garcia-Larrea, Gué not, & Maugui ere, 2001;Maugui ere et al, 1997;Zhu, Disbrow, Zumer, McGonigle, & Nagarajan, 2007). Our findings therefore suggest that visual engagement modulates somatosensory processing, at least, within secondary somatosensory cortex.…”
Section: A Jones B Forster / Neuropsychologia ] (]]]]) ]]]-]]]mentioning
confidence: 60%
See 1 more Smart Citation
“…3). The mid-latency somatosensory P100 is assumed to be generated in bilateral secondary somatosensory cortex (Tarkka, Micheloyannis, & Stokić , 1996;Valeriani, Fraioli, Ranghi, & Giaquinto, 2001;Frot, Garcia-Larrea, Gué not, & Maugui ere, 2001;Maugui ere et al, 1997;Zhu, Disbrow, Zumer, McGonigle, & Nagarajan, 2007). Our findings therefore suggest that visual engagement modulates somatosensory processing, at least, within secondary somatosensory cortex.…”
Section: A Jones B Forster / Neuropsychologia ] (]]]]) ]]]-]]]mentioning
confidence: 60%
“…The P100 is suggested to be a bilateral component originating in secondary somatosensory cortex (Frot et al, 2001;Maugui ere et al, 1997;Zhu et al, 2007) while the origin of the N140 is less clear with multiple areas suggested (Garcia-Larrea, Lukaszewicz, & Mauguiere, 1995), in particular the secondary somatosensory cortex and frontal areas (Allison et al, 1992;Hari & Forss, 1999 Q4 ;Hari et al, 1984;Kakigi et al, 2000;Mima et al, 1998). These two components have repeatedly been demonstrated to be modulated by endogenous tactile attention (P100; Adler, Giabbiconi, & Müller, 2009;Eimer & Forster, 2003a, 2003bZopf, Giabbiconi, Gruber, & Müller 2004), N140; (Adler et al, 2009;Eimer & Forster, 2003a;Forster & Eimer, 2004;Zopf et al, 2004).…”
Section: A Jones B Forster / Neuropsychologia ] (]]]]) ]]]-]]]mentioning
confidence: 99%
“…To achieve the overlays and to determine the source localizations of the SEFs, CURRY multi-modal neuroimaging software (Neuroscan, El Paso, TX, USA) was used. If present, ipsilateral activity was modeled by an extra source that was excluded in further analysis (Zhu et al, 2007). Localization results were accepted only if the explained variance was above 90%.…”
Section: Magnetic Source Imagingmentioning
confidence: 99%
“…From S1, information is sent simultaneously to the secondary PeerJ PrePrints | http://dx.doi.org/10.7287/peerj.preprints.480v1 | CC-BY 4.0 Open Access | rec: 28 Aug 2014, publ: 28 Aug 2014 somatosensory area (S2), the parietal ventral area (PV), the parietal rhinal area (PR), and the contralateral S1 (S1c) (Aronoff et al, 2010) (Krubitzer and Kaas, 1990;Fabri and Burton, 1991;Krubitzer et al, 1995;Disbrow et al, 2000;Remple et al, 2003;Ferezou et al, 2006;Henry et al, 2006; where it is integrated spatiotemporally (Zhu et al, 2007). Similar to S1, areas S2 and PV are organized topographically, with a complete representation of the contralateral half of the body and also receive direct thalamocortical inputs (Liang et al, 2011;Viaene et al, 2011).…”
Section: Introductionmentioning
confidence: 99%